Patterns of peritoneal dissemination and response to systemic chemotherapy in common and rare peritoneal tumours treated by cytoreductive surgery: study protocol of a prospective, multicentre, observational study. Issue 7 (5th July 2021) - Bhatt, Aditi; Rousset, Pascal; Baratti, Dario; Biacchi, Daniele; Benzerdjeb, Nazim; H J T de Hingh, Ignace; Deraco, Marcello; Gushchin, Vadim; Kammar, Praveen; Labow, Daniel; Levine, Edward; Moran, Brendan; et al.
Abstract : Introduction: Despite optimal patient selection and surgical effort, recurrence is seen in over 70% of patients undergoing cytoreductive surgery (CRS) for peritoneal metastases (PM). Apart from the Peritoneal Cancer Index (PCI), completeness of cytoreduction and tumour grade, there are other factors like disease distribution in the peritoneal cavity, pathological response to systemic chemotherapy (SC), lymph node metastases and morphology of PM which may have prognostic value. One reason for the underutilisation of these factors is that they are known only after surgery. Identifying clinical predictors, specifically radiological predictors, could lead to better utilisation of these factors in clinical decision making and the extent of peritoneal resection performed for different tumours. This study aims to study these factors, their impact on survival and identify clinical and radiological predictors. Methods and analysis: There is no therapeutic intervention in the study. All patients with biopsy-proven PM from colorectal, appendiceal, gastric and ovarian cancer and peritoneal mesothelioma undergoing CRS will be included. The demographic, clinical, radiological, surgical and pathological details will be collected according to a prespecified format that includes details regarding distribution of disease, morphology of PM, regional node involvement and pathological response to SC. In addition to the absolute value of PCI, the structures bearing the largest tumour nodules and a description of the morphology in each region will be recorded. A correlation between the surgical, radiological and pathological findings will be performed and the impact of these potential prognostic factors on progression-free and overall survival determined. The practices pertaining to radiological and pathological reporting at different centres will be studied. Ethics and dissemination: The study protocol has been approved by the Zydus Hospital ethics committee (27 July, 2020) and Lyon-Sud ethics committee (A15-128). Trial registration number: CTRI/2020/09/027709; Pre-results.